ELECTRONIC PORTFOLIO AS A MEANS OF FUTURE TEACHERS TRAINING TO PROFESSIONAL ORIENTED WORK - Kovalchuk, Vasyl; Zinchenko, Volodymyr; Sherudylo, Andrii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the publication is to substantiate the pedagogical impact of future teachers electronic portfolio on the quality of vocational guidance in general secondary education. The tasks of the research are solved by the use of methods of analysis of scientific literature, questioning of the educational recipients and scientific and pedagogical workers, testing. The study was conducted at Оlexander Dovzhenko Hlukhiv National Pedagogical University, where 194 undergraduate students of 3-4 courses from pedagogical specialties and 27 scientific and pedagogical staff participated. Students, who studied the disciplines such as "Fundamentals of Scientific Research" and "Fundamentals of Career Orientation" were combined into two groups: experimental and control one. The experimental group consisted of 98 students and the control group consisted of 96 students. The first group created an electronic portfolio while studying those disciplines. The second group has mastered those courses traditionally: lectures and seminars. The test was designed to check students' level of academic knowledge in career guidance, which consisted of questions that had basic aspects of program material. The results of the study show that the use of electronic portfolio helps to ensure the full assimilation of educational material by students and increase the amount of knowledge and practical skills in the implementation of the tasks of vocational guidance in future professional activity.